Requests for Food-provisions in RS 94.2523 and RS 94.2530 - Lyons, Michael C. (Altorientalische Forschungen, 2019)
Scholars have debated the meaning of both RS 94.2523 and 94.2530, two letters from Hatti to Ugarit at the end of the Late Bronze Age. Settling the meaning of the Sumerogram pad (Akkadian, kurummatu ) as either a reference to metal ingots or a type of food-provision has persistently caused interpretative trouble. The present article reassesses Singer’s arguments for reading pad as metal ingots, and it finds his arguments unsupported by the philological evidence. In addition, this article offers a new observation about famine language in RS 94.2530 that suggests pad does indeed refer to food-provisions in both letters as originally proposed by Lackenbacher/Malbran-Labat.